Beauvericin and enniatin B effects on a human lymphoblastoid Jurkat T-cell model. (May 2018) - Manyes, L.; Escrivá, L.; Ruiz, M.J.; Juan-García, A.
Abstract: Several mycotoxins exert their effect on the immunological system; some are classified as immunotoxic. Jurkat T-cells were used to study toxic effects of beauvericin (BEA) and enniatin B (ENN B). Both are not legislated mycotoxins with increasing presence in feed and food. Concentrations studied were from 1 to 15 μM at 24, 48 and 72 h. Cell death by increasing the percentage of apoptotic/necrotic cells was: BEA > ENN B. IC50 values ranged from 3 to 7.5 μM for BEA. ENN B 15 μM decreased viability (21-29%). The percentage of apoptotic/necrotic cells was BEA > ENN B at 24 h but not at 48 h. Caspase-3&7 activation profile varied, although both mycotoxins increased this activation. No difference in ROS production for any mycotoxin was observed. Arrest in S phase for both mycotoxins was obtained. BEA increased the percentage of DNA in the tail (18% and 20%) with respect to the control, whereas not for ENN B. In summary, cytotoxicity of BEA involved mitochondrial alterations; while ENN B only at highest concentrations and time assayed. BEA had cell cycle disturbances and apoptotic and apoptotic/necrotic cells increased; for ENN B these were not evident. Different toxic responses in Jurkat T-cells may be involved in BEA and ENN B toxicity. Highlights: BEA cytotoxicity is mediated through mitochondrial alterations; not always for ENN B. Cell cycle and cell death of BEA is highly affected at doses and times assayed. Jurkat T-cells seem to recover after ENN B treatment while not after BEA treatment. Different toxic responses in Jurkat T-cells may be involved in BEA and ENN B toxicity.